The Transantiago and Its Effect on Pollution (Observatorio Económico, 2013)
There is currently debate as to whether Transantiago buses (Santiago's public transit system) should run on natural gas, a measure that could reduce particulate matter emissions (by up to 80%, according to the Association of Natural Gas Distributors) and help alleviate the pollution problem in the city of Santiago. However, for it to be truly effective, it requires a cost-benefit analysis that considers the costs of implementing a natural gas fleet, the increase it may generate in the price of the fuel, and a comparison with the benefit that a reduction in Transantiago's emissions could bring. It should not be forgotten that, although Transantiago produces pollution, other mobile sources such as cars, trucks, and so on are also an important part of the problem. Continue reading...
Keywords: Transportation system; Transantiago; Pollution